Transition‐Metal‐Free Formal Decarboxylative Coupling of α‐Oxocarboxylates with α‐Bromoketones under Neutral Conditions: A Simple Access to 1, 3‐Diketones1. Issue 3 (20th November 2014) - He, Zhen; Qi, Xiaotian; Li, Shiqing; Zhao, Yinsong; Gao, Ge; Lan, Yu; Wu, Yiwei; Lan, Jingbo; You, Jingsong
Abstract A transition‐metal‐free formal decarboxylative coupling reaction between α‐oxocarboxylates and α‐bromoketones to synthesize 1, 3‐diketone derivatives is presented. In this reaction, a broad scope of substrates can be employed, and neither a metal‐based reagent nor an additional base is required. DFT calculations reveal that this reaction proceeds through a coupling followed by decarboxylation mechanism and the α‐bromoketone unprecedentedly serves as a nucleophile under neutral conditions. The rate‐determining step is an unusual hydrogen‐bond‐assisted enolate formation by thermolysis.